2017
DOI: 10.1021/acssuschemeng.7b00626
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Based Fabrication of Polycrystalline Si Thin-Film Transistors from Recycled Polysilanes

Abstract: Currently, research has been focusing on printing and laser crystallization of cyclosilanes, bringing to life polycrystalline silicon (poly-Si) thin-film transistors (TFTs) with outstanding properties. However, the synthesis of these Si-based inks is generally complex and expensive. Here, we prove that a polysilane ink, obtained as a byproduct of silicon gases and derivatives, can be used successfully for the synthesis of poly-Si by laser annealing, at room temperature, and for n- and p-channel TFTs. The devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…300 °C) in comparison to the ca. 550 °C needed to deposit silicon from SiH 4 . Poly­(dihydrosilane) [SiH 2 ] n has been postulated to be an intermediate in the thermal or photoinitiated ring-opening polymerization (ROP) of cyclo -Si 6 H 12 , a process that eventually yields hydrogenated amorphous bulk silicon (a-SiH) . The formation of [SiH 2 ] n as an orange solid has been documented in the 1980s from the Wurtz-type reductive coupling of H 2 SiCl 2 with Li metal, while treatment of calcium silicide (CaSi) with HCl is reported to give a brown solid with the estimated composition SiH 0.9 .…”
Section: Molecular Hydrides Of the Group 14 Metals (Silicon Germanium...mentioning
confidence: 99%
See 1 more Smart Citation
“…300 °C) in comparison to the ca. 550 °C needed to deposit silicon from SiH 4 . Poly­(dihydrosilane) [SiH 2 ] n has been postulated to be an intermediate in the thermal or photoinitiated ring-opening polymerization (ROP) of cyclo -Si 6 H 12 , a process that eventually yields hydrogenated amorphous bulk silicon (a-SiH) . The formation of [SiH 2 ] n as an orange solid has been documented in the 1980s from the Wurtz-type reductive coupling of H 2 SiCl 2 with Li metal, while treatment of calcium silicide (CaSi) with HCl is reported to give a brown solid with the estimated composition SiH 0.9 .…”
Section: Molecular Hydrides Of the Group 14 Metals (Silicon Germanium...mentioning
confidence: 99%
“…1143 Lastly, heating the germylene-dihydrogermane 939), which reverts back to 938 upon cooling to room temperature. 1142 By increasing the steric bulk of an silyl(aryl)amido substituent, Jones and coworkers were able to prepare the first examples of monomeric two-coordinate Ge(II) hydrides [Ar* Me {( t BuO) 3 Si}N]GeH (942) and [Ar* iPr {( t BuO) 3 Si}N]-GeH (943) by reacting the respective Ge(II) tert-butoxide precursors ( 940) and (941) with catecholborane, HBcat (Scheme 145). 1144 Related alkoxide/hydride metathesis chemistry will be described later in this review, where this reactivity forms the basis of an important activation step within Main Group hydride-mediated catalysis.…”
Section: Catalysis Mediated By Molecular Group 13 Hydridesmentioning
confidence: 99%
“…Therefore, we performed Raman spectroscopy, which enables a larger depth of measurement compared to that of XPS, to confirm the occurrence of the oxidation reaction in the deep internal regions of the electrode. , From the Raman spectra, we observed that the top surface of the Si anode was partially oxidized, while the deep internal region was hardly affected by the HISP flash. The spectra exhibited a single peak centered at 518 cm –1 , indicating that both the VA and FLA samples were composed of polycrystalline Si. …”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] Printed electronics, which have been limited to organic and oxide materials, can be extended to Si semiconductors using liq‐Si, which consists of polysilane solution obtained by polymerization of cyclopentasilane (CPS), [ 8 ] cyclohexasilane, [ 9 ] neopentasilane, [ 10 ] or other hydrosilanes. [ 11 ] The first report of liq‐Si involved poly‐Si transistor fabrication using an inkjet method. [ 2 ] The authors demonstrated the potential of liq‐Si as high‐quality semiconducting Si and also revealed the difficulty of producing a uniform and continuous film by inkjet printing, as only non‐uniform Si films with high roughness were obtained.…”
Section: Figurementioning
confidence: 99%